MEMPROGRAMKAN PENGENALAN BANK SYARIAH DAN LEMBAGA KEUANGAN MIKRO SYARIAH PADA DESA BOJONG JENGKOL, KECAMATAN CIAMPEA, BOGOR - Rully Trihantana; Ria Kusumaningrum; Nina Mulniasari (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2022)
This Community Service was carried out in Bojong Jengkol Village, Ciampea District, BogorRegency, West Java. Bojong Jengkol Village is a village with abundant potential and thereforerequires improving the quality of Human Resources (HR) in cultivate and develop the potential ofthe local village. This community service begins with an observation process village in order tounderstand in depth the potential of the village. Then done planning, implementation, andevaluation. People in the village of Bojong Jengkol still lack of understanding of Islamic banksand Islamic microfinance institutions. Programming the introduction of Islamic banks and Islamicmicrofinance institutions can add further understanding to the community, and their use forfinancing by the community as well. The community service method used is socialization. Withthis activity, it is hoped that the community can be motivated to using Islamic banks and Islamicmicrofinance institutions.